Relationship of Reduced Lung Function in Male Chronic Heart Failure Patients (Anwer Khan Modern Medical College Journal, 2023)
Background: Chronic heart failure (CHF) is a major cause of morbidity and mortality throughout the world affecting multiple organ systems of the body including lungs.Objective: To observe and compare FVC, FEV1 and FEV1/FVC%in CHF patients of different functional classification with healthy individual.Methods: This Cross Sectional study was conducted in the Department of Physiology of Bangabandhu Sheikh Mujib Medical University (BSMMU), Shahbag, Dhaka, during 2016. For this, 60 stable male CHFpatients were randomly selected, these study subjects based on staging of the disease (Stage C) and New York Heart Association (NYHA) functional classification were further divided into two groups, 30 patients of NYHA Class- Iand 30 patients of NYHA class–II. Age, sex and BMI matched, 30 were apparently healthy subjects were taken as control. All the participants were aged 35-65 years.FVC, FEV1 and FEV1/FVC%of all subjects were measured by a portable Digital Spirometer. For statistical analysis, One way ANOVA and Independent sample‘t’ test was performed by using SPSS for windows version-16& p≤ 0.05 was accepted as level of significance.Results: The mean percentage of predicted values of FVC and FEV1 were significantly lower (except FEV1/FVC%) in chronic heart failure patients in comparison to the healthy control. All the study variables were significantly lower in patients of NYHA class–II as compared to patients of NYHA class–I. In addition, 73.33%NYHA class–Ipatientsand 63.33% NYHA class–II patients had restrictive feature.Conclusion: This study concluded thatsomeventilatory variables decrease in CHF patients andto observe extend of lung damage by comparing NYHA class - I and II patients found mild and severe restriction respectively.AKMMC J 2021; 12(1) : 16-21